Wytwórczość włókiennicza w północno-wschodnich Łużycach w XVII-XVIII wieku = Textile manufacture in north-eastern Lusatia in the 17th and 18th century - Partyka, Piotr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the modern period, the job of textile manufacturing in the eastern part of Lower Lusatia was done by municipal guild masters and the rural population. Local raw materials were used, i.e. flax and sheep wool, and since the mid-eighteenth century also imported cotton. The outwork system of production had an effect on the growth of interest in the textile manufacture among peasants.
Keywords: czasopismo; czasopismo akademickie; Ziemie Zachodnie; stosunki polsko-niemieckie; pogranicze polsko-niemieckie; historia